Present and future for information system for monitoring tractability in pork meat supply chain - Popa Liana, Anica; Stoian, Mirela (Economics of Agriculture, 2010)
In the current context of increasing requirements regarding food safety and security and of rapid changes from business environment, the role of information systems for monitoring traceability is in a continuously increase of importance. In order to fulfil the national standards and regulation regarding traceability and the business requirements, it is necessary to be used the most recent development from information technology and communication (IT&C). The data and information provided by information systems must be organized in order to allow a quick extraction and processing for fulfilling the organizations objectives.